An Efficient Approach to approximate the Solutions of Fractional Partial Integro-Differential Equations - A. AbdulKhaleq, Fajir (Al-Nahrain Journal of Science, 2022)
In this article a computational efficient approach is presented so as to examine the approximate solutions (AP) of fractional One-dimensional partial integro-differential equations (CF1DPDEs). The fractional derivative will be in the conformable sense. The suggested approach combined between the shifted Legendre polynomials and a semi-analytic approach. the proposed approach is tested by some examples which are introduced to illustrate its accuracy, applicability and efficiency. Keywords: partial integro-differential equations, conformable fractional derivative, Legendre polynomials.